Passing Before ‘Passing’: The Ambivalent Identity of the Narrator in Johnson’s The Autobiography of an Ex-Coloured Man - Al-Shraah, Bassam M. (European Scientific Journal, ESJ, 2017)
James Weldon Johnson’s The Autobiography of an Ex-Coloured Man is considered by many as an early seminal censure and commentary on the contested racial issue of African American in the United States of America. This paper argues that the ‘invisible’ protagonist of the Novel has passed for white as early as his childhood years. The narrator relinquishes his black identity for the conveniences and supremacy that the white identity entails. This paper brings to question the credibility of narrative in the novel; also, it proves that the narrator contradicts himself. The invisible narrator appears not to have a firm stance regarding the atrocities suffered by his own people—African Americans. People of color in the United States were caught between two cultures, identities, and lives. The un-named narrator has taken the least troubled road. He announces his passing for white at the end of the novel. This study contends that he has done so long time ago before he literally announces his passing.